2022
DOI: 10.3390/ijerph191912809
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Constraint-Induced Movement Therapy (CIMT) on Functional Ambulation in Stroke Patients—A Systematic Review and Meta-Analysis

Abstract: Constraint-induced movement therapy (CIMT) has been delivered in the stroke population to improve lower-extremity functions. However, its efficacy on prime components of functional ambulation, such as gait speed, balance, and cardiovascular outcomes, is ambiguous. The present review aims to delineate the effect of various lower-extremity CIMT (LECIMT) protocols on gait speed, balance, and cardiovascular outcomes. Material and methods: The databases used to collect relevant articles were EBSCO, PubMed, PEDro, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The limitations in the usage of the hand may further affect trunk stability [ 54 , 55 ]. The positive associations between the trunk and upper limb impairment observed in the present study suggested evaluating and minimizing the upper limb impairments and encouraging the utilization of the upper limb, which in turn can reduce the upper limb impairments and improve the trunk control, functional balance, and gait functions in late subacute stage [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limitations in the usage of the hand may further affect trunk stability [ 54 , 55 ]. The positive associations between the trunk and upper limb impairment observed in the present study suggested evaluating and minimizing the upper limb impairments and encouraging the utilization of the upper limb, which in turn can reduce the upper limb impairments and improve the trunk control, functional balance, and gait functions in late subacute stage [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that some of the trends observed reflect a type II statistical error due to the small number of experiments for some of the assays. While our study only focused on forelimb immobilization, lower-limb immobilization has also been studied at the clinical level in stroke and related conditions [ 26 ]. Clinical studies of lower-limb immobilization have claimed to improve leg function, although whether this necessarily improves balance and gait speed has been debated.…”
Section: Discussionmentioning
confidence: 99%
“…Constraint-induced movement therapy (CIMT) is a rehabilitation therapy designed to improve upper limb motor function after stroke . In animal and clinical studies, CIMT is widely used to improve the affected limb function after stroke by forcing the use of the affected limb and restricting the use of the healthy side. , However, the mechanisms of CIMT are still unclear. It is necessary to explore the pathophysiological mechanism of rehabilitation therapy for a cerebral stroke.…”
Section: Introductionmentioning
confidence: 99%